Plant cells express telomerase activity upon transfer to callus culture, without extensively changing telomere lengths - Fajkus, J; Fulnecková, J; Hulánová, M; Berková, K; Ríha, K; Matyásek, R (Molecular & general genetics, 1998)
Changes in telomere lengths and telomerase activity in tobacco cells were studied during dedifferentiation and differentiation; leaf tissues were used to initiate callus cultures, which were then induced to regenerate plants. While no significant changes in the range of telomere lengths were observed in response to dedifferentiation and differentiation, there was a conspicuous increase in telomerase activity in calli compared to the source leaves, where the activity was hardly detectable. In leaves of regenerated plants, the telomerase activity fell to almost the same level as in the original plant, showing on the average 0.04% of the level in callus. The process was then repeated using the regenerants as the source material. In the second round of dedifferentiation and differentiation, telomerase activity showed a similar increase in calli derived from regenerated plants and a drop in plants regenerated from these calli. Telomere lengths remained unchanged both in calli and in leaves of regenerants. The conservation of telomere lengths over repeated rounds of dedifferentiation and differentiation, which are associated with dramatic changes in cell division rate and corresponding variation in telomerase activity may reflect the function of a regulatory mechanism in plant cells which controls telomerase action to compensate for replicative loss of telomeric DNA.
Keywords: listy rostlin; Plants, Toxic; buněčná diferenciace; kultivované buňky; Cells, Cultured; jedovaté rostliny; Nicotiana; telomerasa; Telomerase; tabák; telomery; Telomere; Cell Differentiation; Plant Leaves